Computational wind engineering 1 : proceedings of the 1st International Symposium on Computational Wind Engineering (CWE92), Tokyo, Japan, August 21-23, 1992 - Murakami, Shuzo, 1942- (Elsevier, 1993)
The aim of this volume is to explore the challenges posed by the rapid development of Computational Fluid Dynamics (CFD) within the field of engineering. CFD is already essential to research concerned with fluid flow in civil engineering, and its further potential for application in wind engineering is highly promising. State-of-the-art papers from all over the world are contained here, illuminating the present parameters of the field, as well as suggesting fruitful areas for further research. Eleven papers have been contributed by invited speakers outstanding in the fields of CFD and wind engineering. This volume will serve as a vehicle to promote further development in computational wind engineering.